Разработка и апробация комплексного метода оптимизации ступени осевой турбины - Бойко, Анатолий Владимирович; Усатый, Александр Павлович; Максюта, Дмитрий Игоревич (НТУ "ХПИ", 2015)
В статье приведен комплексный метод оптимизации ступени осевой турбины, объединяющая в себе одномерную и трехмерную оптимизацию. Представлен алгоритм оптимизационного процесса. По разработанной методике выполнена оптимизация ступени осевой турбины для различных радиальных зазоров. В результате оптимизации заметно повышен КПД изолированной ступени. Сделан анализ причин увеличения эффективности.

This scientific paper describes an algorithm used by the integrated method for the axial turbine stage optimization, which is based on the iteration process of the alternating use of the methods of one-dimensional and three-dimensional optimizations under the condition of the conservation of the flow rate. A turbine stage model (a prototype of the third stage of the high pressure cylinder of the steam turbine K-500-65/3000) with two sizes of radial clearances (0,5 mm and 1,0 mm) was optimized. The developed algorithm showed a stable tendency to an increase in the efficiency factor both in the case of one-dimensional and three-dimensional optimizations. The obtained data were analyzed. The efficiency factor of the stage in the case of one-dimensional optimization is increased due to the nozzle array and working cascade losses and exit velocity losses. This is reached due to the optimal selection of the reactivity factor on the mean radius. The three-dimensional optimization allows for the determination of the optimal laws of the blade vortex and the height leveling of the flow shock incident on the working cascade. The use of the optimization algorithm allowed us to increase the efficiency factor of the stage by 0.56 % in absolute values at a radial clearance of 0.5 mm and by 35 % at a radial clearance of 1,0 mm. The analysis carried out to define the reasons for an increase in the efficiency factor of the stage would hold for both values of radial clearances, which are indicative of the high accuracy of the developed method and that it can be used for the wide range of the structures of turbine stages.
Developing and testing the integrated method used for the axial turbine stage optimization
Keywords: оптимизационный процесс; турбинная ступень; периферийная протечка; закон закрутки; optimization method development; turbine stage; peripheral leakage; vortex law